Risk Factors for Adult Depression: Adverse Childhood Experiences and Personality Functioning - Dagnino, Paula; Ugarte, María José; Morales, Felipe; González, Sofia; Saralegui, Daniela; Ehrenthal, Johannes C. (Frontiers in Psychology, 2020)
Background: Depressive disorder is one of the main health problems worldwide. Many risk factors have been associated with this pathology. However, while the association between risk factors and adult depression is well established, the mechanisms behind its impact remain poorly understood. A possible, yet untested explanation is the mediating impact of levels of personality functioning, i.e. impairments with regard to self and interpersonal. Method: 162 patients were assessed at the beginning of their therapy, with regard to risk factors, such as sociodemographic, physical, hereditary (Information Form), and adverse childhood experiences (CTQ). Depressive symptoms (BDI), and personality functioning (OPD-SQ) were also measured. Associations between the related variables as well as other possible covariates were examined by means of zero-order correlations and bootstrapping-based mediation analysis. Results: Of all the risk factors taken into account, level of education and physical illness were associated with depression. On the other hand, the most significant predictor of depressive symptomatology was Adverse Childhood Experiences (ACE), and this relationship was mediated by personality functioning. This indicates that patients presenting adverse childhood experiences are more likely to develop deficiencies in personality functioning, which in turn increases their likelihood of developing depressive symptomatology. Conclusion: These results reaffirm the importance of incorporating risk and vulnerability factors such as personality functioning in understanding depression.